45.5k views
2 votes
Which two of the following mapping statements describe the same translation?

O 6.-9) - (0,1)
0 (-3,7) (-9,10)
(1, -5) (-5, -2)
(2, 4) + (-4,1)

1 Answer

4 votes

Answer:

The mapping statements (-3,7) -> (-9,10) and (1, -5)-> (-5, -2) describe the same translation.

Explanation:

In a translation, we have that:

(x,y) -> (x+a,y+b)

In which a and b are how much the values change.

(6.-9) -> (0,1)

x subtracted by 6, y added by 10. So, the translation rule is:

(x,y) -> (x - 6, y + 10).

(-3,7) -> (-9,10)

x subtracted by 6, y added by 3. So

(x,y) -> (x - 6, y + 3).

(1, -5)-> (-5, -2)

x subtracted by 6, y added by 3. So

(x,y) -> (x - 6, y + 3)

Same rule as the above, so the mapping statements (-3,7) -> (-9,10) and (1, -5)-> (-5, -2) describe the same translation.

(2, 4) -> (-4,1)

x subtracted by 6, y subtracted by 3. So

(x,y) -> (x - 6, y - 3)

User Yesnik
by
4.8k points